2020
DOI: 10.1002/wer.1371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of impressed current cathodic protection systems on chemical characteristics of underground water

Abstract: Despite well-known corrosion inhibition behavior of cathodic protection (CP) system, this process might be a potential hazard to surrounding ecosystem resulted mostly from continuous electrical current which is applied to the adjacent environment and metallic anode dissolution as well. In this research, deepwater CP wells at different locations of Golestan province, Iran, were taken into consideration to evaluate the impact of these protective systems on underground waters from viewpoint of chemical and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is probable for as-developed discharge channels to be fabricated on their former counterparts activating the sparks over the surface haphazardly and blocking adjacent channels. Even though a tiny percent of surface pores could develop to the substrate-coating interface, they were likely to be blocked by the molten material and subsequent solidification [59,60]. There is also an apparent difference between the coating and the electrolyte temperature as they reach thousands of degrees and 30-40 • C during plasma electrolytic oxidation, respectively.…”
Section: Characterization Of Current Density During the Peo Processmentioning
confidence: 99%
“…It is probable for as-developed discharge channels to be fabricated on their former counterparts activating the sparks over the surface haphazardly and blocking adjacent channels. Even though a tiny percent of surface pores could develop to the substrate-coating interface, they were likely to be blocked by the molten material and subsequent solidification [59,60]. There is also an apparent difference between the coating and the electrolyte temperature as they reach thousands of degrees and 30-40 • C during plasma electrolytic oxidation, respectively.…”
Section: Characterization Of Current Density During the Peo Processmentioning
confidence: 99%
“…The mass loss results from two distinct phenomena-the oxidation of iron and the solubilization of oxidized compounds in the aqueous environment-and, likely, the former is a faster phenomenon than the dissolution of corrosion products. The hydrogen peroxide, being very concentrated, acts as a strong oxidant, even without adding acids, but the process proceeds in stages and initially, the metallic iron is oxidized to Fe 2+ , which is later oxidized to Fe 3+ , in water solution [27]. An electrochemical process takes place and the surface of steel acts as an anode where atoms of iron are oxidized and released in solution.…”
Section: Corrosion Experimentsmentioning
confidence: 99%
“…Moreover, High silicon cast iron that can be used as an anode to prevent ship corrosion. 24 The presence of nano silica in ultra-highperformance concrete effectively is delayed the initiation of corrosion of the steel bars. The LPR and Tafel results is confirmed that the nano silica embedded bars increased the polarization resistance and reduced the corrosion rate.…”
Section: Cathodic Protection Systemmentioning
confidence: 99%